Pengorganisasian Supervisi Akademik di SMK Negeri Tanjungsari - Raharjo, Sujoko Budi; Hasan, Yetri; Thahir, Andi; Ayu, Sovia Mas; Junaidah, Junaidah (Attractive : Innovative Education Journal, 2022)
This study aims to describe the academic supervision of school principals in improving teacher performance at SMKN Tanjungsari, South Lampung Regency. A phenomenological approach with a case study design was used in this field research using data collection techniques through observation, interviews with school principals, vice principals in the academic field, vice principals in quality management, Islamic Religious Education subject teachers. The results showed that good management of school principals in academic supervision which included planning, organizing and supervising resulted in an increase in teacher performance which could be seen in the many types of activities carried out and the many school members involved. Keywords: Academic Supervision, Teacher Performance, School Principle